Role of Aplysia Cell Adhesion Molecules During 5-HT-Induced Long-Term Functional and Structural Changes - Han, Jin-Hee (Cold Spring Harbor Laboratory Press, 2004)
We previously reported that five repeated pulses of 5-HT lead to down-regulation of the TM-apCAM isoform at the surface of Aplysia sensory neurons (SNs). We here examined whether apCAM down-regulation is required for 5-HT-induced long-term facilitation. We also analyzed the role of the cytoplasmic and extracellular domains by overexpressing various apCAM mutants by DNA microinjection. When TM-apCAM was up-regulated in SNs by DNA microinjection, five pulses of 5-HT failed to produce either synaptic facilitation or an enhancement of synaptic growth, suggesting that down-regulation of apCAM is required for 5-HT-induced EPSP enhancement and new varicosity formation. However, disrupting the extracellular domain function of overexpressed apCAM with a specific antibody restored 5-HT-induced excitatory postsynaptic potential increase but not synaptic growth. The overexpression of the MAP Kinase mutant of TM-apCAM, which is not internalized by 5-HT, inhibited new varicosity formation, but did not inhibit excitatory postsynaptic potential increase. Deletion mutants containing only the cytoplasmic portion of apCAM blocked 5-HT-induced synaptic growth but not excitatory postsynaptic potential increase. Thus, our data suggest that TM-apCAM may act as a suppressor of both synaptic-strength enhancement in pre-existing synapses and of new synaptic varicosity formation in the nonsynaptic region, via different mechanisms.